Coincidental detection of T-cell rich B-cell lymphoma in the paraaortic lymph nodes of a woman undergoing lymph node dissection for cervical cancer. Issue 4 (1st June 2003) - Abali, H.; Eren, O. O.; Erman, M.; Uner, A. H.; Kose, F.; Guler, N.
Abstract : The diagnosis of cervical squamous cell carcinoma with concurrent T-cell rich B-cell lymphoma in dissected lymph nodes has not been reported to our knowledge. We report such a case. The biopsy of an exophytic lesion at the uterine cervix showed squamous cell carcinoma in a 50-year-old woman presenting with postcoital bleeding. Type III hysterectomy, bilateral salpingo-oophorectemy, bilateral pelvic, paraaortic lymph node dissections were performed. Pathologic examination revealed a T-cell rich B-cell lymphoma in some lymph nodes beside squamous cell carcinoma in several of others. ELISA for human immuno-deficiency virus (HIV) was negative. The cervical carcinoma was staged as FIGO clinical stage IB1 and the lymphoma as Ann Arbor IIA. Six cycles of CHOP (cyclophosphamide, adriamycin, vincristine, and prednisone) chemotherapy for the lymphoma and concomitant pelvic chemo-radiotherapy with cisplatin for cervical cancer were given. In this rare coincidence; the best available therapy for each of the diseases should be considered individually. We also suggest that HIV screening test be carried out, because both diseases may be related to human immuno-deficiency virus, although our patient was HIV-negative.